Pembuatan Video Tempat-Tempat Angker di Tanjungpinang - Kho, Jensen; Deli, Deli (Universitas Putera Batam, 2022)
Many things have advanced in today's world as a result of sophisticated technology, one of which is video media. Video is a kind of communication that uses moving images and sound to convey information. The word